Development of a nurse-manager dualistic intervention program to alleviate burnout among nurses based on the appreciative inquiry - Guo, Yu-Fang; Wang, Xin-Xin; Yue, Fang-Yan; Sun, Feng-Ye; Ding, Min; Jia, Yan-Nan (Frontiers in Psychology, 2022)
Aims To develop a feasible and effective nurse-manager dualistic intervention program to support nurses coping with burnout symptoms. Background Person-organization combined interventions were recommended as the most effective approach for reducing burnout symptoms. However, few interventions have been developed in the nursing field. Methods The Medical Research Council, United Kingdom (MRC UK), Framework for Development and Evaluation of Complex Interventions, was employed for nurse-manager dualistic intervention program development. The following three steps were followed for developing the dualistic intervention program: (1) identifying the evidence base by conducting extensive reviews of the relevant literature and a mixed study; (2) identifying/developing a theory by selecting the job demands-resources model and proposing the theoretical framework for intervention development; and (3) modifying the process and outcomes of the nurse-manager dualistic intervention program. Results The intervention program consists of six group sessions over 9 weeks. Researchers/managers are supposed to deliver the program. The main contents of the intervention are (1) inception (session 1); (2) discovery (session 2); (3) dream (session 3); (4) design (session 4); (5) destiny (session 5); and (6) keep (session 6). The emphasis of the intervention is on helping nurses dealing with burnout symptoms. Conclusion Following the guidance of the MRC framework, a feasible and potentially effective nurse-manager dualistic intervention program was developed for nurses coping with burnout. Future studies are needed to model the intervention and assess the effects and replicability of the intervention.